KNOWLEDGE, ATTITUDE AND PRACTICES OF CARDIOPULMONARY RESUSCITATION AMONG NURSES - NASIR , D; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Cardiopulmonary resuscitation (CPR) is a critical life-saving skill that significantly impacts patient outcomes during cardiac emergencies. Nurses, being at the forefront of emergency care, play a vital role in performing CPR effectively. This study aimed to assess the knowledge, attitudes, and practices of nurses regarding CPR in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 140 nurses working in the Intensive Care Unit (ICU) and emergency departments of a tertiary care hospital. Data were collected using a structured, pre-validated questionnaire consisting of demographic information, knowledge assessment, attitudes, and practices related to CPR. Statistical analysis, including descriptive and inferential methods, was performed using SPSS version 26. Results: The study reported that participants with good knowledge were 70(50.0%), the participants with moderate knowledge were 35(25.0%), and the participants with poor knowledge were 35(25.0%). Participants with positive attitude were 102(72.9%), and the participants with negative attitude were 38(27.1%). The participants with good practice were 90(64.3%), and the participants with poor practice were 50(35.7%). Conclusion: While nurses demonstrated moderate knowledge and positive attitudes toward CPR, significant gaps in specific practices were identified. Targeted training programs, regular competency assessments, and policy reforms are essential to enhance nursing competencies and ensure effective CPR performance, ultimately improving patient outcomes.